PENGARUH PERAN KELOMPOK TANI TERHADAP KOHESIVITAS DI KELOMPOK TANI TRANGGULASI DESA BATUR, KECAMATAN GETASAN, KABUPATEN SEMARANG - Gabriella, Eunice; Satmoko, Sriroso; Mardiningsih, Dyah (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 1 (2020): Vol. 14 No. 1, 2020DO - 10.24843/SOCA.2020.v14.i01.p03, 2020)
The advanced farmer group that have many members, did not guarantee that the members of the group has intemacy value. Closed relation farmer members group would be shown by the strength of the farmer group role. The research aim was to identify the farmer groups role and the cohesiveness of organic vegetable farming system. The other research aim was to analyze the role of farmers groups influence on the cohesiveness of Tranggulasi organic vegetables farming system. The research was conducted at Tranggulasi farmer group, Desa Batur on 12-29 Mey 2018. Survey method was used and samples were conducted with 32 people of active members in farmer gtoup. The results showed that the farmer groups roles as learning class was in good category with percentage 53%, coorperation action was 63%, and unit of production was 69%. The cohesiveness of organic vegetable farming was good category with percentage 81%. Multiple linear regression test showed that the learning class, cooperation action, and unit of production, has significant effect on the cohesiveness of organic vegetable farming.